2021
DOI: 10.1158/0008-5472.can-20-3892
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ADAM10 by Radiation Therapy Drives Fibrosis, Resistance, and Epithelial-to-Mesenchyal Transition in Pancreatic Cancer

Abstract: Stromal fibrosis activates prosurvival and proepithelial-to-mesenchymal transition (EMT) pathways in pancreatic ductal adenocarcinoma (PDAC). In patient tumors treated with neoadjuvant stereotactic body radiation therapy (SBRT), we found upregulation of fibrosis, extracellular matrix (ECM), and EMT gene signatures, which can drive therapeutic resistance and tumor invasion. Molecular, functional, and translational analysis identified two cell-surface proteins, a disintegrin and metalloprotease 10 (ADAM10) and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…[39][40] In addition, combined modality approaches that may help address pathways of therapeutic resistance to radiation should also be explored. 41 Limitations inherent to our study include its retrospective, single-arm, and single-institution nature. Furthermore, with respect to surgical margins, it remains a matter of debate how specimens are processed and analyzed, and it remains unclear what constitutes a truly positive margin especially in a population that has received neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40] In addition, combined modality approaches that may help address pathways of therapeutic resistance to radiation should also be explored. 41 Limitations inherent to our study include its retrospective, single-arm, and single-institution nature. Furthermore, with respect to surgical margins, it remains a matter of debate how specimens are processed and analyzed, and it remains unclear what constitutes a truly positive margin especially in a population that has received neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described the role of stromal fibrosis in activating pro-survival and epithelial-to-mesenchymal transition (EMT) pathways in PDAC. The group identified two cell-surface proteins, a disintegrin and metalloprotease 10 (ADAM10) and ephrinB2, as drivers of fibrosis and tumor progression after radiation therapy (RT) and suggested that activation by ephrinB2 drives fibroblasts toward a myofibroblast differentiation, thereby driving cancer invasion ( Mueller et al, 2021 ). Unfortunately, there are few studies that include data on fibroblast heterogeneity and/or phenotype with respect to resistance to RT and most studies focus more on the mechanisms underpinning RT resistance in general; as such, this section will be a more general viewpoint on the role of CAFs in mediating/alleviating radioresistance in PDAC.…”
Section: The Tumor Stroma and Radioresistancementioning
confidence: 99%
“…In this way chemokine receptors that are induced by activation are likely to be enriched on the antigenspecific populations in the tumor environment, akin to the activation markers CD69 and CD39. It may also be important that CXCL16 is an unusual chemokine in that it is membrane bound, until cleaved by proteases that are regulated under inflammatory conditions and during cancer treatment (84)(85)(86)(87). Therefore, CXCR6 may generate a retentive niche for antigenreactive cells in close contact with epithelial cells, or recruitment from systemic circulation under inflammatory conditions.…”
Section: Chemokine Modification Of Tumors To Increase Recruitmentmentioning
confidence: 99%